Supply response of potato in Bangladesh: a vector correction approach - A. S. M. Anwarul Huq,; Mohamed Arshad, Fatimah (Asian Network for Scientific Information, 2010)
An attempt has been made in this study to examine the supply response of potato in Bangladesh by using the vector error correction approach. The short-run price elasticity was 0.45 while the long run elasticity was 0.62. Price policies are effective in obtaining the desired level of output for potato. If intervention in the market is of necessity, then it must be implemented during the harvest season for altering price expectations. Also emphases should be given to increase potato export and establishing export oriented potato processing industries.